Electronic Transitions in Conformationally Controlled Tetrasilanes with a Wide Range of SiSiSiSi Dihedral Angles. Issue 30 (14th July 2014) - Tsuji, Hayato; Fogarty, Heather A.; Ehara, Masahiro; Fukuda, Ryoichi; Casher, Deborah L.; Tamao, Kohei; Nakatsuji, Hiroshi; Michl, Josef
Abstract Unlike π‐electron chromophores, the peralkylated n‐tetrasilane σ‐electron chromophore resembles a chameleon in that its electronic spectrum changes dramatically as its silicon backbone is twisted almost effortlessly from the syn to the anti conformation (changing the SiSiSiSi dihedral angle ω from 0 to 180°). A combination of UV absorption, magnetic circular dichroism (MCD), and linear dichroism (LD) spectroscopy on conformationally controlled tetrasilanes 1–9, which cover fairly evenly the full range of angles ω, permitted a construction of an experimental correlation diagram for three to four lowest valence electronic states. The free chain tetrasilane n‐Si4Me10 (10), normally present as a mixture of three enantiomeric conformer pairs of widely different angles ω, has also been included in our study. The spectral trends are interpreted in terms of avoided crossings of 1B with 2B and 2A with 3A states, in agreement with SAC‐CI calculations on the excited states of 1–7 and conformers of 10.